IMPACT OF COMPENSATION, CAREER DEVELOPMENT, PERFORMANCE APPRAISAL AND TRAINING ON PERFORMANCE OF EMPLOYEES IN BATAM - Yuswardi Yuswardi; Suryanto Suryanto (Program Sarjana Manajemen Universitas Internasional Batam, 2021)
Performance of employees is the result of employees' efforts and efforts to achieve work performance that fulfills their obligations to the company. The common goal of the company is to get the benefits that can be achieved with the help of high performance employees.This research was conducted by distributing 275 questionnaires which then obtained 265 feedback from respondents regarding the performance of employees at supermarket companies in Batam. The results of data collection from respondents were tested using SPSS.From the test results it is known that there is a significant positive relationship in all tested variables in accordance with the formulated hypothesis. The results of this study are expected to enrich research related to human resource management and be useful for company management in evaluating the factors that affect employee performance.